The efficiency and tolerability of lacosamide therapy in adolescents and adults with new-onset focal epilepsy in terms of the epileptiform activity index - V. A. Karlov; P. N. Vlasov; A. B. Kozhokaru; A. S. Samoilov; A. S. Orlova (Неврология, нейропсихиатрия, психосоматика, 2020)
Lacosamide (LCM) is one of the most promising antiepileptic drugs (AEDs) for focal epilepsy (FE); however, in Russia there are only a few works devoted to its practical application.Objective: to evaluate the efficiency of LCM therapy in adolescents and adults with new-onset FE.Patients and methods. The investigation enrolled 36 patients aged 16-78 years. All the patients underwent video-ECG monitoring with quantification of the epileptiform activity index (EAI) at baseline and 1, 3, 6 and 12 months of treatment. The treatment efficiency was evaluated using the standard measures: drug-induced remission, a response rate of ≥50%, an insufficient efficiency of ≤50%, higher seizure frequency, and therapy retention rates. Adverse events (AEs) were assessed using the SIDe-effects of AntiEpileptic Drugs (SIDAED) questionnaire.Results and discussion. Just 3 months after starting treatment, the total EAI substantially decreased from 2.92 [0; 6.7] to 1.95 [0; 3.07] (p<0.05). LCM demonstrated a high efficacy and a good tolerance in the therapy of FE: by the end of 12-month follow-up, there was a considerable decrease in EAI by 1.57 times (p<0.05); the LCM monotherapy retention rate of 72.2% was achieved in 26 patients: 20 (55.6%) patients had drug-induced remission; six (16.7%) patients were responders. AEs were recorded in 5 (13.8%) cases.Conclusion. LCM is an effective AED for the initial monotherapy of FE. The use of LCM in FE causes a considerable decrease in EAI by 1.57 times (p<0.05).